The Status of Using Blended Learning in Teaching the English Language at High Schools from the Teachers’ Point of View - Al-Momani, Amal Mohammad (Journal of Curriculum and Teaching Methodology, 2023)
The purpose of this research is to acknowledge the status of using blended learning in teaching at high schools from the teacher's point of view. The researcher used the descriptive analytical approach which is more appealing in its methods to the nature of the study, its variables, and its goal. The researcher chose for her study society English teachers working at the university schools in the capital for the academic year 2020/2021, about 147 teachers. The researcher study class sample was chosen randomly and the estimated number of teachers was about 109. The researcher managed to achieve a number of conclusions, resulting in clarifying that teachers are more into using multimedia as tools for their methods in teaching English language curriculum at high school instead of the traditional tools for teaching.
Keywords: Blended teaching; high school